2014
DOI: 10.1089/hum.2014.099
|View full text |Cite
|
Sign up to set email alerts
|

SelectiveIn VivoTargeting of Human Liver Tumors by Optimized AAV3 Vectors in a Murine Xenograft Model

Abstract: Current challenges for recombinant adeno-associated virus (rAAV) vector-based cancer treatment include the low efficiency and the lack of specificity in vivo. rAAV serotype 3 (rAAV3) vectors have previously been shown to be ineffective in normal mouse tissues following systemic administration. In the present study, we report that rAAV3 vectors can efficiently target and transduce various human liver cancer cells in vivo. Elimination of specific surface-exposed serine and threonine residues on rAAV3 capsids res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 54 publications
4
46
0
Order By: Relevance
“…Additionally, we have generated tyrosine-mutant rAAV3B serotype vectors, and identified an optimized vector that efficiently transduces human liver tumours in a murine xenograft model in vivo 13 . In an attempt to further enhance the transduction efficiency of rAAV3B vector, we evaluated AAV3B vectors A c c e p t e d m a n u s c r i p t human liver tumor cells and primary human hepatocytes in vitro 14,15 . Moreover, the use of the rAAV3B-ST vectors not only led to targeted delivery and suppression of human liver tumorigenesis in a murine xenograft model, in our preliminary studies, it also resulted in efficient transduction of primary human humanized murine livers in vivo 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we have generated tyrosine-mutant rAAV3B serotype vectors, and identified an optimized vector that efficiently transduces human liver tumours in a murine xenograft model in vivo 13 . In an attempt to further enhance the transduction efficiency of rAAV3B vector, we evaluated AAV3B vectors A c c e p t e d m a n u s c r i p t human liver tumor cells and primary human hepatocytes in vitro 14,15 . Moreover, the use of the rAAV3B-ST vectors not only led to targeted delivery and suppression of human liver tumorigenesis in a murine xenograft model, in our preliminary studies, it also resulted in efficient transduction of primary human humanized murine livers in vivo 14 .…”
Section: Introductionmentioning
confidence: 99%
“…All rights reserved(S663V+T492V) in the AAV3B capsid that significantly augmented the transduction efficiency of these vectors in liver cancer cells in a xenograft mouse model in vivo13,15 in primary human hepatocytes in vitro; and in humanized mouse and NHP models in vivo, it should be noted that this most efficient mutant was identified from among 10 different permutations and combinations using a single human cancer cell line, Huh7, in vitro 15 . Thus, it remains possible that one or more of the mutant AAV3B vectors will be optimal in transducing primary human hepatocytes in humanized mouse and NHP models in vivo.…”
mentioning
confidence: 99%
“…In our previously published studies, we identified the S663V+T492V doublemutant (DM) AAV3 vector as the most efficient vector in transducing human liver cancer cell lines. 25 Thus, the following sets of DM-ssAAV3-Fluc vectors were generated: DM-ssAAV3-WT-Fluc; DM-ssAAV3-LC1-Fluc and DM-ssAAV3-LC2-Fluc vectors was increased by up to 6-fold at such a low MOI.…”
Section: Resultsmentioning
confidence: 99%
“…To date only one member of the family, AAV serotype 3, has been found to have specificity for human hepatocytes and human liver cancer cells. AAV3 vectors have been shown to be able to discriminate between human liver cancer cells and mouse hepatocytes in xenograft animal model in vivo (25,30,40).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic modifications of these regions increases the efficiency of transduction of AAV vectors in different tissues and cells types, most likely by preventing phosphorylation of these residues, and subsequent degradation of the vectors by host proteasome machinery. These studies have led to the development of several AAV vectors with higher activity in a variety of cell and animal models (17, 20, 22-26, 28, 30 Priority was given to the positions which are conserved among various serotypes, and have previously shown a better performance for other AAV vectors (17,22,23,28,30) (Table 1).…”
Section: Insertion Of Rgd Peptide Into Aav6 Capsid Improves Vector-mementioning
confidence: 99%